The Impact of Sustainability in Enhancing the Performance of Construction Companies - LECHVIEN, AMATARAHMAAN (İstanbul Kültür Üniversitesi, 2025)
This study explores the impact of corporate sustainability on corporate performance. The research involved 3,612 managers working in construction companies, and the random sampling (RS) method was applied. The minimum required sample size was 347 managers. A total of 400 questionnaires were distributed, 346 of which were returned, while 54 were not returned. Ultimately, 319 questionnaires were usable, yielding a response rate of 79.75%. The results showed that corporate sustainability, in its social, environmental, and economic dimensions, has a significant positive effect on corporate performance. Specifically, corporate social, environmental, and economic responsibility all have a significant positive impact on corporate performance. The study suggests that future research should examine factors that mediate or moderate the relationship between corporate social, environmental, and economic responsibilities and corporate performance. Factors such as organizational culture, leadership style, stakeholder engagement, and technological adoption could provide further insights into the dynamics influencing these relationships.
Keywords: Corporate Sustainability; Corporate Social; Environmental; Economic Responsibility Corporate Performance; Construction Companies